Deep Institutional Innovation for Sustainability and Human Development. Issue 5 (4th July 2021) - Hughes, Ian; Byrne, Edmond; Glatz-Schmallegger, Markus; Harris, Clodagh; Hynes, William; Keohane, Kieran; Gallachóir, Brian Ó.
Abstract: The present moment of deep transition, as well as being a time of danger, presents an opportunity for positive renewal. This paper develops a model of deep institutional innovation at times of historic change such as the present and outlines a research agenda aimed at initiating a holistic assessment of the main foundational institutions in society and re-imagining them in ways that will allow them to fulfill their basic ethical and effectiveness functions. Such a fundamental critique and re-imaging, the paper argues, is essential if global challenges are to be mitigated and resolved.